Diffusive Metrics Induced by Random Affinities on Graphs. An Application to the Transport Systems Related to the COVID-19 Setting for Buenos Aires (AMBA) - Acosta, M. F.; Aimar, H.; Gómez, I.; Morana, F. (Trends in Computational and Applied Mathematics, 2022)
The aim of this paper is to apply the diffusive metric technique defined by the spectral analysis of graph Laplacians to the set of the 41 cities belonging to AMBA, the largest urban concentration in Argentina, based on public transport and neighborhood. It could be expected that the propagation of any epidemic desease would follow the paths determined by those metrics. Our result reflects that the isolation measures decided by the health administration helped at the atenuation of the actual spread of COVID-19 in AMBA.